Optimalisasi Peran PKK dalam Peningkatan Ekonomi Keluarga Dusun Pajangan, Sendangsari, Bantul, DIY (Lembaga Pengembangan Kinerja Dosen, 2026)
This Community Service Program aims to optimize the role of the Family Welfare Empowerment (PKK) organization in improving the family economy as an effort to support family welfare and resilience. Family economic resilience plays an important role in preventing various social and health problems, including stunting, which remains a concern in community development. The program was implemented in Panjangan Hamlet, Sendangsari, Bantul, Special Region of Yogyakarta, with local PKK members as the primary target participants. The activities were carried out through entrepreneurship counseling, financial literacy training, and assistance in preparing simple bookkeeping for household businesses. This program was designed to enhance the capacity of PKK members in managing businesses and family finances more effectively. The results indicated an improvement in participants’ understanding of household business management, simple financial record-keeping, and more systematic family financial planning. In addition, participants gained practical knowledge and skills that could be utilized to support increased family income. Through this program, PKK members are expected to optimize their family economic potential, thereby fostering sustainable economic independence. Furthermore, the program is expected to contribute to the development of more prosperous, empowered, and resilient rural communities.